Simple Technique for Augmentation of the Facial Soft Tissue - Francesco Inchingolo; Marco Tatullo; Fabio M. Abenavoli; Massimo Marrelli; Alessio D. Inchingolo; Roberto Corelli; Raffaella Mingrone; Angelo M. Inchingolo; Gianna Dipalma (The Scientific World Journal)
Due to the request of numerous patients to improve the aspect of the perioral area in combination with other types of cosmetic and reconstructive surgery, we started to use autologous fillers. In fact, there are numerous potential fillers that can be utilized during various operations executed in many bodily areas, such as the breast, abdomen, and face. The muscular fascia as well as the dense connective tissue which the surgeon encounters in various bodily areas during some stages of the operation, in fact, can be removed and replaced both by themselves or superimposed in order to increase their thickness. The insertion of the grafts is carried out by using a needle, but other methods can also be used with the same success. The consistency of the area treated, after a few days of edema, is very similar to the host area, and the volume obtained remains uniform in time (our followup is after 24 months). The time utilized for the removal and the insertion in the chosen area was only a few minutes. The result was extremely satisfactory in all the 30 patients treated, and there was no complication or side effects.